Oracle DBA automation quick reference - Russel, Charlie (Prentice Hall, 2004)
Part of the PHPTR Oracle Series . Fast, easy automation for every Oracle 9i and 10g DBA! Quick access to real-world examples. Installation, database creation, management, monitoring, tuning, and backup/recovery. Oracle Universal Installer (OUI), Oracle Net Configuration Assistant (NetCA), and Oracle Database Configuration Assistant (DBCA)